Evaluation de l’activité cicatrisante et de la toxicité aigue de l’extrait aqueux de l’Atriplex halimus chez le rat wistar - BENYECHOU, Yamina Mansouria; ELAHOUEL, Naziha (My University, 2021)
In this study, aqueous extract from the leaves of Atriplex halimus was studied for acute toxicity and healing activity in Wistar rats. For the study of acute toxicity, the extract was administered in a dose of 5g / kg in unique dose, per Os to Wistar rats. The rats were monitored for 48 hours. The LD50 was over 5mg/kg. In the excision wound model, rats were classified into 4 groups of five rats each. Lot 1 served as a control, lot 2 received a standard treatment (MADECASSOL ointment) and Lot 3 treated with cream base only (exipient) while Lot 4 was treated with a cream based on Atriplex halimus leaf extract at a dose of 5% (study group). Healing activity was evaluated by estimating the reduction in the surface area of the wound, the time required for complete epithelialization, and the resistance to skin rupture. The histological study of the granulation tissue was performed to determine the extent of collagen formation in the wound tissue. In the excision wound, animals treated with Atriplex halimus cream showed a significant reduction (P < 0.001) in the area of the wound and a faster rate of epithelialization compared to controls. In addition, histological studies showed significantly higher activity in the 2 groups treated with plant-based cream and MADECASSOL compared to the other groups. Our study found that the Atriplex-based preparation has a powerful healing activity.
Keywords: healing activity, Atriplex halimus, acute toxicity, leaf, wounds